O22 Using mental simulation as preparation for surgery; an interventional study exploring its effects on surgical team performance and non technical skills. (3rd November 2019) - Gabbott, Ben; Biggs, Alexandra; Snelgrove, Huon; Tennent, Duncan
Abstract : Introduction: Mental Simulation (MS) is a broad term used to cover a variety of preparatory actions used by clinicians in clinical practice, to visualise a task prior to performance. It has been defined as 'the cognitive rehearsal of a task in the absence of overt physical movement'. 1 Anecdotally, we know clinicians rely on MS prior to performing difficult tasks, especially when true simulation type equipment isn't available. 2 While widely performed and accepted in other areas of expertise (sports, aviation etc), Medicine has been slow to incorporate it into its educational frameworks. Though in recent years, a body of evidence has began to prove that it can be used to augment and improve surgical individual performance. 3 The conundrum here however, is that preventable errors in healthcare rarely occur due to technical mistake or individual performance. Poor teamwork and its relatable non-technical skills (NTS) (communication, situational awareness etc) is a much larger driving force in the prevention of harm to patients. 4 We hypothesis that a group MS task, focussed on NTS, performed by the entire surgical team prior to performing an operation will result in better NTS, and thus theatre team performance. This may result in better outcomes and thus results for patients. Methods: A two-part, longitudinal, interventional, real world study was performed. Part A of the study involved the video recording of a trauma and orthopaedic surgical team performing carpal tunnel procedures, as they would normally in clinical practice. This was then assessed using observational teamwork scores (OTAS) and assessing the number of surgical errors. Surgical team members were also asked to fill out a mental readiness questionnaire (mMIQ) and a safety attitude questionnaire (ORMAQ). Part B of the study involved the theatre team performing a 15 min MS of a carpal tunnel procedure prior to operating. The theatre was then video recorded again and the same outcomes recorded for comparison. Results: All data has been fully collected, and currently being analysed by statisticians. Early reports look promising in favour of MS. Discussions and conclusions: Pre-operative MS has the potential to provide a free, quick and widely accessible tool to augment team performance in theatre. This could potentially decrease the number of surgical errors, improving the team's performance and thus improve patient outcomes and safety. References: Driskell JE, Moran A. Does Mental Practice Enhance Performance? Journal of Applied Psychology 1994:481–92. 4. Rao A, Tait I, Alijani A. Systematic review and meta-analysis of the role of mental training in the acquisition of technical skills in surgery. Am J Surg 2015;210(3):545–53. Kohn LT, Corrigan JM, Donaldson MS. To Err is Human - Building a Safer Health System. Washington DC: National Academies Press (US).